Penerapan Strategi 'Akhbārīyah' untuk Meningkatkan Kemampuan Bahasa Arab Siswa Kelas V SDN Puspan Maron Probolinggo - Dewi Putri Nafila; Ainur Rofiq Sofa (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to describe the implementation of the "Akhbārīyah" strategy in teaching Arabic news text reading and to analyze its impact on improving the Arabic language skills of fifth-grade students at SDN Puspan Maron Probolinggo. The research employed a quantitative approach with a quasi-experimental design. Instruments used included observations, reading skill tests, and documentation. The results indicated that the implementation of the "Akhbārīyah" strategy significantly enhanced students' reading abilities, expanded their vocabulary, and improved their understanding of Arabic sentence structures. Furthermore, this strategy increased students' motivation and interest in learning Arabic through engaging and contextual news texts. These findings suggest that the "Akhbārīyah" strategy is effective as an alternative method for enhancing Arabic language skills at the elementary school level.